PERKUATAN LENTUR PELAT LANTAI BETON BERTULANG DENGAN MENGGUNAKAN KABEL BAJA DAN MORTAR - , INDRIYANI PULUHULAWA; , Dr. -Ing. Ir. Djoko Sulistyo ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Changes in building functions is one of the issue that often arises at this point. In order to maintain the structure of the building a lot of research being done to address the problem of changes in the function of the building. One method is by doing retrofitting of on the structure of the building. This research aims to determine the bending capacity, stiffness, ductility and crack pattern of the floor slab, reinforced with the addition of steel cables as tensile bars, self-compacting mortar and dyna bolt as a shear connector (stud). In this research two test object slab used that is slab reinforcement using steel cable diameter of 10 mm (PP 10) and slab reinforcement using steel cable of diameter 8 mm (PP 8) test specimen used as a comparison control plate (PK) without reinforcement (Hartono , 2009). Two test object has the same dimensions of 1500 mm x 700 mm x 100 mm and using the main reinforcement steel reinforcement prior to retrofitting the plain 10 mm diameter 140 mm distance to the quality of concrete (fc ') = 28,5 MPa for PK and fc results of flexural strength testing test object PP 10 and PP 8 respectively- contributed 32,1 kN and 26,7 kN. By comparing to the slab before retrofitting or control slab (PK) test object of PP 10 and PP 8 bending capacity decreased respectively by 34,06% and 17,73%. Comparison of bending capacity of research results and Response-2000 Program to test object PP 10 and PP 8 respectively 59,13% and 30,24%. Comparison of bending capacity of research and analysis of the SNI method to test object PP 10 and PP 8 respectively 56,92% and 32,7%. Increasing the value of stiffness in the test specimen PP 10 and PP 8 respectively 779,8% and 480,33% when compared to the control slab (PK). Ductility of test object PP 10 and PP 8 decreased to the control slab, each for 60,49% and 16,67%. In general, the pattern of collapse that occurred at PP 10 and PP 8 is the failure of debonding/delamination. ' = 43,8 MPa for PP 8 and PP 10. To testing the test object is placed on a loading frame with simlpy supported at both ends of test specimens and given static load at midspan with a 1 kN intervals until the specimen reaches collapsed. The results were then compared with the theoretical analysis based on SNI and Response-2000 program.